SERUM FERRITIN LEVEL AND MYELOPEROXIDASE ACTIVITY IN TYPE 2 DIABETIC MALES ON ORAL HYPOGLYCEMIC AGENTS - VIPLAV PRASHANT; MEERA K S (International Journal of Pharma and Bio Sciences, 2014)
Diabetes mellitus is the most common endocrine disorder, characterised by hyperglycemia caused by absolute or relative deficiency of insulin. Chronic hyperglycemia and enhanced oxidative stress have been implicated in the pathogenesis of diabetic vascular complications. The objective of the study was to find if there is an association between serum ferritin level and serum myeloperoxidase activity in type 2 diabetic males. Serum ferritin level was estimated by ELISA method and serum myeloperoxidase activity by spectrophotometric method using O-dianisidine dihydrochloride as substrate. A significant rise in serum ferritin level (p < 0.001) and myeloperoxidase activity (p<0.001) with associated hyperglycemia, is an indicator of inflammatory process in diabetics. Hemoglobin level was within physiological range. There was a significant positive correlation between serum myeloperoxidase activity and serum ferritin level (p < 0.001). The increased level of myeloperoxidase activity can further contribute to the accelerated progression of atherosclerosis in diabetic mellitus.